Microchannel Flow Dynamics and Heat Transfer of Near-Critical Fluid - Chen, Lin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book discusses basic thermodynamic behaviors and 'abnormal' properties from a thermo-physical perspective, and explores basic heat transfer and flow properties, the latest findings on their physical aspects and indications, chemical engineering properties, microscale phenomena, as well as transient behaviors in fast and critical environments. It also presents the most and challenging problems and the outlook for applications and innovations of supercritical fluids. .
Introduction -- Design and Realization of Near-Critical Transient Visulization Experiment -- Discussion of Near-Critical Heat Transfer Flow Experiments -- Numerical Formulation of Near-Critical CO2 Flow in Microchannels -- Heat Transfer Charicteristics of Near-Critical Microchannel Flows -- Theoretical Analysis of Near Critical Stability Behaviors -- Summary and Outlook.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Microtechnology; Microelectromechanical systems; Electric power production; Continuum mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Microsystems and MEMS; Electrical Power Engineering; Mechanical Power Engineering; Continuum Mechanics